Effect of KF absorber treatment on the functionality of different transparent conductive oxide layers in CIGSe solar cells. (16th August 2017) - Keller, Jan; Chalvet, Francis; Joel, Jonathan; Aijaz, Asim; Kubart, Tomas; Riekehr, Lars; Edoff, Marika; Stolt, Lars; Törndahl, Tobias
Abstract: This contribution studies the impact of the KF‐induced Cu(In, Ga)Se2 (CIGSe) absorber modification on the suitability of different transparent conductive oxide (TCO) layers in solar cells. The TCO material was varied between ZnO:Al (AZO), ZnO:B (BZO), and In2 O3 :H (IOH). It is shown that the thermal stress needed for optimized TCO properties can establish a transport barrier for charge carriers, which results in severe losses in fill factor ( FF ) for temperatures >150°C. The FF losses are accompanied by a reduction in open circuit voltage ( V oc ) that might originate from a decreased apparent doping density ( N d, app ) after annealing. Thermally activated redistributions of K and Na in the vicinity of the CdS/(Cu, K)‐In‐Se interface are suggested to be the reason for the observed degradation in solar cell performance. The highest efficiency was measured for a solar cell where the absorber surface modification was removed and a BZO TCO layer was deposited at a temperature of 165°C. The presented results highlight the importance of well‐designed TCO and buffer layer processes for CIGSe solar cells when a KF post deposition treatment (KF‐PDT) was applied. Abstract : In order to optimize the electro‐optical properties of transparent conductive oxide layers like ZnO:B or In2 O3 :H, elevated deposition or annealing temperatures are required. This contribution shows that the corresponding thermal stress leads to a significant deterioration in the performance of Cu(In, Ga)Se2 solar cells if they were subjected to a KF post deposition treatment (KF‐PDT). It is suggested that a thermally induced redistribution of K (and possibly Na) leads to a creation of a transport barrier and a decrease in doping density.